Common-Mode Impedance Stabilizing Device Applied to the Output of Railroad Traction Inverters in the Evaluation of Conductive Emissions - Satoru Hatsukade; Keiji Wada (IEEE Access)
We present a new device called a common-mode impedance stabilizing device (CMISD), which is applied to the output of inverters installed in railroad vehicles. The proposed device is used in the evaluation of the disturbance voltage in conductive emissions; its purpose is to stabilize the common-mode (CM) impedance ( $150~± ~20~Ω $ ) in the 100 kHz – 10 MHz frequency range, which corresponds to the operating frequencies of railroad signaling devices called “balises.” The balises are installed on railroad tracks and used for communication between trains and wayside systems, and electromagnetic compatibility between rolling stock and the balises are severe problem. In the design of the CMISD, we considered two factors: the ferrite core size of the CM inductor and the heat dissipation in the resistors. In the CM inductor, we assumed realistic conditions to reduce its core mass to ~3.4 kg. Regarding heat dissipation, considering that the negative terminal of a railroad vehicle with DC feeding voltage must be grounded, we assumed that square-wave peak voltage is applied directly to the CM circuit of the CMISD. The experimental results showed that the power dissipation in the CR series circuit in the CMISD was proportional to the carrier frequency, capacitance, and the square of the line voltage. Eventually, we fabricated a prototype CMISD, which can withstand the heat generated when applying a 750-V DC input voltage at a 3-kHz carrier frequency for five minutes.